A study on the demand for high-level talent recruitment in tertiary public hospitals in Chongqing based on the Kano model - Liu, Meng; Wen, Siyu; Dai, Shujie; Deng, Quanxin; Li, Jing (Frontiers in Public Health, 2025)
ObjectiveThis study examines the recruitment demands for high-level talent at tertiary public hospitals in Chongqing, providing scientific evidence to assist hospital administrators in formulating optimized strategies for attracting such personnel.MethodA stratified random sampling method was employed to investigate the recruitment demands for high-level talent in tertiary public hospitals in Chongqing. Quantitative analysis was conducted using the Kano model and Better-Worse matrix analysis.ResultsThe Kano analysis identified that among the 20 high-level talent recruitment demands, the majority were categorized as one-dimensional and attractive demands, with only talent incentive schemes, career development opportunities, and performance appraisal systems being must-be demands. The Better-Worse analysis revealed 6 must-be, 5 attractive, 6 one-dimensional, and 3 indifferent demands. Ranked according to the priority of high-level talent recruitment demands, the top five demands are: a scientifically sound and reasonable performance appraisal system; opportunities for professional development; talent incentive measures; receiving respect and care; and generous remuneration packages.ConclusionIn the recruitment of high-level talents, Must-be demands are the core factor, One-dimensional demands are the paramount priority, and attractive demands serve as supplementary factors. When formulating talent recruitment strategies, hospital administrators should adopt targeted measures to prioritize fulfilling the must-be demands of high-level talents, enhance their one-dimensional demands, and elevate their attractive demands. They must fully consider the importance and priority of different demands, identify the key strengths and weaknesses in talent acquisition, and continuously and dynamically monitor shifts in the demands of high-level talent.